Analysis of a Commercial Structure Utilizing Analysis Tool Staad.Pro - Vijay Singh Dasoondi; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2021)
Now a days multi-storey buildings constructed for the purpose of residential, commercial, industrial etc., with an open ground storey has become a common feature. For the sake of parking, the ground storey is kept free without any constructions, except for the columns which transfer the building weight to the ground. For a hotel or commercial building, where the lower floors contain banquet halls, conference rooms, lobbies, show rooms or parking areas, large interrupted space is required for the movement of people or vehicles. The columns which are closely spaced in the upper floors are not advisable in the lower floors. So to avoid this problem, floating column concept has come into existence The examination was centered around breaking down the impacts of coasting segments when upheld on different example of shafts in a G+6 story structure in thinking about seismic zones III and delicate soil condition utilizing Staad.Pro.v8i. The investigation of skimming segments was finished considering the boundaries to be specific the base shear, story uprooting, story float and story speed increase concerning subject multi-story structure with various situation of supporting pillar just beneath the gliding segments.
Keywords: Floating Columns; STAAD.Pro; Story Drift; Base Shear; Story Displacement